The Australian Pelvic Floor Questionnaire is a valid measure of pelvic floor symptoms in patients following surgery for colorectal cancer. Issue 5 (24th October 2016) - Lin, Kuan‐Yin; Frawley, Helena C.; Granger, Catherine L.; Denehy, Linda
Abstract : Aims: This study evaluated the construct validity of the Australian Pelvic Floor Questionnaire against two alternative measures of the severity of bladder and bowel symptoms. Methods: This was an exploratory analysis of data from two prospective studies. Patients who had undergone surgery for colorectal cancer were analysed. Bladder and bowel symptoms were measured using three validated questionnaires: the Australian Pelvic Floor Questionnaire, the International Consultation on Incontinence Questionnaire Short Form Questionnaire for urinary incontinence and the International Consultation on Incontinence Questionnaire‐Bowel Module post‐cancer treatment. Results: The study sample consisted of 44 participants, including 25 men and 19 women. The Australian Pelvic Floor Questionnaire bladder and bowel domain scores demonstrated moderate positive correlations with the International Consultation on Incontinence Questionnaire Short Form Questionnaire for urinary incontinence ( r  = 0.74, P  < 0.01) and the International Consultation on Incontinence Questionnaire‐Bowel Module ( r  = 0.69–0.78, P  < 0.01). Similar results were obtained in each gender subgroup. Conclusions: This study suggested that the Australian Pelvic Floor Questionnaire may be a valid measurement tool for use in colorectal cancer populations in clinical trials and practice. Future research using larger cohorts is warranted.